Mobile wallets and virtual currencies - Pickens, Mark; Richardson, Brian (Technical Centre for Agricultural and Rural Cooperation, 2007)
For more than a decade IT advocates in the North have been predicting that cash, debit cards and credit cards will soon be replaced by mobile phones. While there is little sign that this is happening in the North, in many developing countries the story is very different